1984
DOI: 10.2134/jeq1984.00472425001300020008x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Biota to Organic Amendments in Stripmine Spoils in Northwestern New Mexico

Abstract: We examined the effects of organic amendments and topsoiling on the soil biota and decomposition in order to evaluate the relative efficacy of the amendments in restarting soil processes. We studied decomposition of barley straw (Hordeum vulgare) and populations of soil biota on strip coal‐mine spoils in northwestern New Mexico. The spoils had been amended with straw mulch, bark, topsoil, or no organic additives. Decomposition rates were highest in the unmined area and the bark, amended spoils (K = 0.64 yr−1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…He emphasized that organic matter is the key to stable microbial activity in arid and semiarid ecosystems. Several other studies have also confirmed that the addition of recalcitrant organic matter to disturbed soil results in higher rates of decomposition and mineralization through the development of soil microorganisms comparable to those of undisturbed systems (Elkins et al 1984;Ingham et al 1985;Smith et al 1986;Schuman & Belden 1991). Though there have been studies of the nitrogen cycle of several California ecosystems (Bartolome 1979;Jackson & Roy 1986;Jackson et al 1988;Davidson et al 1990;Hart et al 1993), little research on the effects of organic matter amendments has been performed in southern California, and no literature could be found on the effect of recalcitrant organic matter on soil fungi in this area.…”
Section: Discussionmentioning
confidence: 74%
“…He emphasized that organic matter is the key to stable microbial activity in arid and semiarid ecosystems. Several other studies have also confirmed that the addition of recalcitrant organic matter to disturbed soil results in higher rates of decomposition and mineralization through the development of soil microorganisms comparable to those of undisturbed systems (Elkins et al 1984;Ingham et al 1985;Smith et al 1986;Schuman & Belden 1991). Though there have been studies of the nitrogen cycle of several California ecosystems (Bartolome 1979;Jackson & Roy 1986;Jackson et al 1988;Davidson et al 1990;Hart et al 1993), little research on the effects of organic matter amendments has been performed in southern California, and no literature could be found on the effect of recalcitrant organic matter on soil fungi in this area.…”
Section: Discussionmentioning
confidence: 74%
“…However, their biochemical activities can be slow to re-establish (Chodak, 2009) and may take several decades to reach stable conditions normally found in native soils (Chatterjee et al, 2009;Insam and Domsch, 1988). Soil carbon amendments stimulate microbiological activity (Bendfeldt et al, 2001;Elkins et al, 1984;Lindemann et al, 1984), as can the establishment of herbaceous plants using the additions of fertilizers and lime (Chaudhuri et al, 2015). However, as easily decomposable organic matter is rapidly consumed, an overall decline of microbial activity results if no further additions of external nutrients and organic matter are applied because a reservoir of soil organic matter is lacking in newly created mine soils (Stephens et al, 2001;Stroo and Jencks, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Once returned to the ground, the faecal mass stimulates the activity of soil biota, increasing mineralisation of plant-essential nutrients (Elkins et al 1994;Steinberger et al 1984). Nutrient returns to the soil via excreta will vary with the length of time spent by livestock in the pasture, rate of excretion and decomposition time (Hirata et al 2011).…”
mentioning
confidence: 99%